Why Does Conservation Fail Without Inner Transformation? Perspectives from Sufism and Ecology: Mengapa Konservasi Gagal Tanpa Transformasi Batin? Perspektif Tasawuf dan Ekologi - Siti Aisah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2026)
This study examines Sufism (tasawuf) as a spiritual ethical framework for environmental conservation, arguing that the ecological crisis is also rooted in a crisis of meaning and moral consciousness. Employing a descriptive qualitative literature study, data were collected through systematic reviews of classical Sufi texts and contemporary works on Islam and ecology, and analyzed using close reading, thematic interpretation, and conceptual comparison. The findings highlight three main results: (1) Sufi ecology is grounded in the tauhid–khalifah–mizan framework, which interprets nature as sacred signs (ayat kauniyah), positions humans as trustees, and emphasizes balance; (2) inner transformation toward pro-environmental behavior operates through tazkiyah al-nafs, zuhud, and qana’ah, which regulate the ego-driven impulses underlying overconsumption and waste; and (3) relational ethics and practical implementation are reinforced by mahabbah–rahmah and internalization practices (muraqabah, gratitude, wara’), which can be institutionalized through education, faith-based communities, and sufficiency-oriented economic practices. The study implies that conservation efforts may become more sustainable when supported by spiritual character formation and social institutionalization of Sufi values. The originality lies in proposing an integrative model linking theological foundations, inner-change mechanisms, and social implementation pathways of eco-Sufism, offering an operational basis for environmentally oriented Sufi psychotherapy/Islamic counseling.